RESULTS OF COMPLEX TREATMENT OF VARIOUS TRAUMA OF FRONTAL SINUS - Boymuradov Sh.A.; Bakieva Sh.Kh.; Karimberdiev B.I.; Djuraev J.A. (International Journal of Medical Science and Public Health Research, 2025)
This article presents the results of comprehensive treatment for patients with combined injuries of the nose and paranasal sinuses. Combined craniocerebral injuries vary. First aid is provided first, i.e., bleeding from wounds is stopped, the wound is firstly surgically treated and sutured. Simultaneous symptomatic treatment is performed. Respiration, blood pressure, heart and brain activity will be restored. If there is a hematoma of the brain, a craniotomy is first performed to prevent complications, bleeding is stopped, and only then is planned treatment performed.